The Sephardim Diaspora: A Model of Forced Migration and Confiscation - Joao Ricardo Faria (University of Kent, Department of Economics, 1998)
This paper studies the expulsion of Jews from Spain in 1492. This forced migration process is addressed with a model that blends demographic, religious and macroeconomic features. The optimal migration path is derived. It is shown that a large portion of the Sephardim community fled the country and, given the confiscation process they suffered, their final income was smaller than the income just before the expulsion. The model provides several predictions: (1) the rate of growth of the country falls with the migration; (ii) an increase in the inflation rate decreases the final income of the Jews; (iii) the government has an incentive to denerate inflation since this minimises the negative impact of the diaspora on the rate of growth; and (iv) the decision to reduce the activities of the Spanish Inquisition diminished the migration.
Keywords: D99; J19; J61; J79; 330; Migration; Confiscation; Discrimination; Migrationspolitik; Auswanderung; Antisemitismus; Juden; Spanien